Genetic and epigenetic variation in the DNMT3B and MTHFR genes and colorectal adenoma risk. (8th April 2016) - Ho, Vikki; Ashbury, Janet E.; Taylor, Sherryl; Vanner, Stephen; King, Will D.
Abstract : Polymorphisms in DNMT3B and MTHFR have been implicated in cancer etiology; however, it is increasingly clear that gene‐specific DNA methylation also affects gene expression. A cross‐sectional study (N = 272) investigated the main and joint effects of polymorphisms and DNA methylation in DNMT3B and MTHFR on colorectal adenoma risk. Polymorphisms examined included DNMT3B c.−6‐1045G > T, and MTHFR c.665C > T and c.1286A > C. DNA methylation of 66 and 28 CpG sites in DNMT3B and MTHFR, respectively, was quantified in blood leukocytes using Sequenom EpiTYPER®. DNA methylation was conceptualized using two approaches: (1) average methylation and (2) unsupervised principal component analysis to identify variables that represented methylation around the transcription start site and the gene coding area of both genes. Logistic regression was used to estimate odds ratios (ORs) and 95% confidence intervals (CIs) associated with the main and joint effects of polymorphisms and DNA methylation. DNA methyltransferase 3B (DNMT3B) TT versus GG/GT genotypes was associated with increased colorectal adenoma risk (OR = 2.12; 95% CI: 1.03–4.34). In addition, increasing DNA methylation in the gene‐coding area of DNMT3B was associated with higher risk of colorectal adenomas (OR = 1.34; 95% CI: 1.01–1.79 per SD). In joint effect analyses, synergistic effects were observed among those with both the DNMT3B TT genotype and higher DNMT3B methylation levels compared to those with GT/GG genotypes and lower methylation levels (OR = 4.19; 95% CI: 1.45–12.13 for average methylation; OR = 4.26; 95%CI: 1.31–13.87 for methylation in the transcription start site). This research provides novel evidence that genetic and epigenetic variations contribute to colorectal adenoma risk, precursor to the majority of colorectal cancer (CRC). Environ. Mol. Mutagen. 57:261–268, 2016. © 2016 Wiley Periodicals, Inc.